The Role of Work Community, Career Growth, and Employee Well-Being on Employee Engagement in Malaysian SMEs - Bawazir , Abdullah Abdulaziz; Munap, Rudzi Binti; Rajan, Sharmila Saundara; Munusamy, Kalaiselvan; Ramakrishnan, Dhiviya Bharathi P. (Business Management and Strategy, 2024)
This study explores the factors influencing employee engagement within Small and Medium-sized Enterprises (SMEs) in Klang Valley, Malaysia. It focuses on three key dimensions: work community, career growth opportunities, and employee well-being, analyzing their relationships with employee engagement levels. Surveys were conducted among SME employees, and correlation analyses were used to examine these associations. The study targeted 200 employees from four service SMEs in the Klang Valley. Based on Krejcie & Morgan’s table, a sample size of 132 was needed, but to address potential response issues, 145 questionnaires were distributed. The findings reveal significant positive correlations between the work community, career growth opportunities, and employee well-being with employee engagement. These results underscore the critical importance of fostering supportive work environments that encourage collaboration, provide clear pathways for career advancement, and prioritizing employee well-being through comprehensive wellness programs. The study’s implications suggest practical strategies for SMEs to enhance organizational effectiveness and employee satisfaction. By focusing on these factors, SMEs can create environments that promote higher levels of engagement, ultimately contributing to organizational success. Future research could explore additional variables impacting employee engagement across different sectors and regions, further enriching the understanding of effective engagement strategies in diverse organizational contexts. This study offers valuable insights for SME leaders and HR professionals aiming to improve employee engagement and organizational performance.